BENTUK KOMUNIKASI SIMBOLIK TARI REJANG LILIT PADA UPACARA DEWA YAJNA DI DUSUN TANAH EMBET KABUPATEN LOMBOK BARAT - NI NYOMAN HARNIKA (Universitas Mahasaraswati Mataram, 2020)
Arts creativities can be categorized as nyolahang sastra activity. That is because the performance of art is a medium for the delivery of religious teachings and interactions with others. The community of Tanah Embet Hamlet implements communication in rejang convolution dance through various dance movements as symbols, a form of non verbal communication that is full of meaning. The purpose of this study is to analyze and describe the process and form of communication of the symbolic dance of twisted rejang dance. Data collection is done by means of observation, interviews, documentation. Data analysis used descriptive analysis The results showed that the symbolic communication forms of the rejang lilit dance in the deity of Yajña in Tanah Embet were (1) transcendent communication in the verbal form of spells and in the form of nonverbal offerings; (2) interpersonal communication in the form of nonverbal gong sounds; (3). Group communication in the form of verbal words stakeholders or languages and in the form of non-verbal dance movements twisted rejang.